BEHAVIORAL INTENTION USING ONLINE FOOD DELIVERY SERVICE: INFORMATION TECHNOLOGY CONTINUANCE APPROACH - Dewi Sri Woelandari Pantjolo Giningroem; Naili Farida; Harry Soesanto (International Journal of Business and Society, 2023)
The surge of online food delivery (OFD) services is emblematic of the restaurant industry’s presence in the e-delivery landscape. Further, this research reveals that comprehending consumer decision-making processes necessitates the appraisal of consumer behavior perception. Thus, this study aims to scrutinize the impact of hedonic motivation, convenience motivation, and post-usage usefulness on consumer interest and behavior towards OFD services, moderated by their attitudes towards using such services. To achieve this objective, a purposive sample of 150 students who have used OFD services was gathered and analyzed using a quantitative approach. Empirical data was collected via questionnaires, and a structural equation modeling (SEM-AMOS) was employed to examine the empirical model. The findings of this study suggest that hedonic motivation, convenience motivation, post-usage usefulness, and attitudes towards OFD were key determinants of OFD service behavioral intention. The swift expansion of fast food in Indonesia can be attributed to advancements in telecommunication infrastructure and internet users, lower smartphone prices, as well as the convenience and accessibility of mobile phones and the internet. This phenomenon has been capitalized on by fast food companies, who have leveraged online food delivery (OFD) services to cater to the surging demand.